Risk factors for surgical site infection following laparotomy: Effect of season and perioperative variables and reporting of bacterial isolates in 287 horses. (4th February 2016) - Isgren, C. M.; Salem, S. E.; Archer, D. C.; Worsman, F. C. F.; Townsend, N. B.
Summary: Reasons for performing study: Surgical site infection (SSI) is an important cause of post operative morbidity following laparotomy. Objectives: To investigate risk factors for SSI, including effect of season and surgery performed outside normal working hours, and to report bacterial isolates and antimicrobial resistance patterns. Study design: Retrospective cohort study. Methods: Data were obtained from horses that had undergone exploratory laparotomy over a 3‐year period (2010–2013) in a UK hospital population. SSI was defined as any purulent or serous discharge from the laparotomy incision of >24 h duration that developed during hospitalisation. Multivariable logistic regression was used to identify associations between pre‐, intra‐ and post operative variables and altered likelihood of SSI. Results: Surgical site infection developed in 73/287 (25.4%) horses during hospitalisation. Horses of greater bodyweight (odds ratio [OR] 1.002, 95% confidence interval [CI] 1.0002–1.005, P = 0.03), increased packed cell volume (≥48%) on admission (OR 3.03, 95% CI 1.32–6.94, P = 0.01), small intestinal resection (OR 2.27, 95% CI 1.15–4.46, P = 0.02) and post operative colic (OR 2.86, 95% CI 1.41–5.79, P = 0.003) were significantly associated with increased likelihood of SSI in a multivariable model. SSI was also significantly more likely to occur during winter (OR 3.84, 95% CI 1.38–10.70, P = 0.01) and summer (OR 5.63, 95% CI 2.07–15.3, P = 0.001) months in the model. Three‐layer closure of the incision was protective (OR 0.31, 95% CI 0.16–0.58, P<0.001) compared to 2‐layer closure. There was no effect of surgery being performed outside normal working hours (P = 0.5). The most common bacterial isolates were Escherichia coli (59.5%), Enterococcus spp. (42.4%) and Staphylococcus spp. (25.4%). Penicillin resistant isolates accounted for 92% (96/104) of isolates while 18% (21/119) of isolates were gentamicin resistant. Conclusions: Laparotomy during winter and summer months was associated with increased likelihood of SSI but there was no effect of surgery performed outside normal working hours. This information assists in identifying horses at high risk of SSI and informing development of preventive strategies.